2020
DOI: 10.21272/fmir.4(3).72-79.2020
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth and the Optimal Size of the Public sector in Jordan

Abstract: The relationship between the size of public sector and the rate of economic growth has been widely examined empirically in different countries. Most applied studies confirmed the validity of the inverse relationship between the increasing role of the state in the economy, measured by the ratio of public spending to gross domestic product and rates of economic growth. These studies estimated the optimum rate that would guarantee achieving the highest economic growth rates. This study aims to analyses this relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…Armey (1995) concluded that the relationship between government size and economic growth takes the form of an inverted (U) shape. All field studies except the study conducted by Fallahi and Shoorkchali (2012) have proved the validity of Armey's relationship, which is an inverse relationship between the size of the government as measured by the ratio of public expenditure to GDP and the rate of economic growth, as stated by Aljaloudi and Warrad (2020).…”
Section: Literature Reviewmentioning
confidence: 89%
“…Armey (1995) concluded that the relationship between government size and economic growth takes the form of an inverted (U) shape. All field studies except the study conducted by Fallahi and Shoorkchali (2012) have proved the validity of Armey's relationship, which is an inverse relationship between the size of the government as measured by the ratio of public expenditure to GDP and the rate of economic growth, as stated by Aljaloudi and Warrad (2020).…”
Section: Literature Reviewmentioning
confidence: 89%
“…Every measurement should serve a purpose while measuring a business process -one should have a specific goal to improve the process efficiency. The head of the organization can achieve better performance that ensures the sustainable competitive benefit of the business process by making a large-scale assessment of the key elements of the process and then aligning the performance measures with the strategic goals and purposes [38].…”
Section: Supplier Effectivenessmentioning
confidence: 99%
“…A wide range of mathematical methods is used for modelling economic, political, social, and informational development. Scientists have solved these problems by building optimization models [37], structural modelling [38], gravity modelling [39], using data mining methods [40], fuzzy sets [41], regression analysis [42]- [43], probabilistic methods [44], econometric tools [45], statistical analysis [46], methods for implementing integer arithmetic operations [47], pseudo-random sequence [48]. It is necessary to use a more specific method, such as determining the center of mass, to model sustainable growth.…”
Section: Problem Formulationmentioning
confidence: 99%